RBM15 Functions in Blood Diseases - Hu, Mengyu; Yang, Yuxia; Ji, Zhi; Luo, Jianyuan (Current cancer drug targets, 2016)
RBM15, an RNA-binding protein, plays important roles in the growth and apoptosis of cells, especially blood cells through regulating multiple signal pathways such as Notch and Wnt. An increasing body of evidence has suggested that RBM15 may play a key function on the development of various blood diseases, such as acute/chronic myeloid leukemia and kaposi's sarcoma. In this review, we will focus on the progress of the association between RBM15 and its related blood diseases.